Direct growth of triple cation metal-organic framework on a metal substrate for electrochemical energy storage - Nurul Khairiyyah, Mohd Zain; Vijayan, Bincy Lathakumary; Izan Izwan, Misnon; Das, Santanu; Karuppiah, Chelladurai; Yang, Chun-Chen; M. M., Yusoff; Rajan, Jose (American Chemical Society (ACS Publications), 2019)
Metal−organic frameworks (MOFs) offer a robust structure with high surface area together with open metal center sites which easily undergo the reversible redox reaction without damaging the framework; therefore, they are actively considered as a medium for electrochemical energy storage. This article demonstrates the superiority of triple cation metal-terephthalate as charge storage electrodes over their single component counterparts. We report the preparation of ternary metalterephthalate (CoCuNi-bdc/NF) containing equimolar precursors of Co, Cu, and Ni as metal centers and terephthalic acid (H2 bdc) as the organic linker and its single metal counterparts (Cobdc/NF, Cu-bdc/NF, and Ni-bdc/NF) on Ni-foam substrate via a one-step facile hydrothermal reaction. The structure and morphologies of the CoCuNi-bdc/NF composite and its single component counterparts are characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and field-emission scanning electron microscopy techniques. The charge storage capabilities of the electrodes are evaluated by cyclic voltammetry, charge−discharge cycling, and electrochemical impedance spectroscopy in an aqueous alkaline electrolyte (6 M KOH) in a three-electrode system (half-cell) configuration. The specific capacity of CoCuNibdc/NF was ∼321.3 mA h g−1 (∼2892 F g−1), which is over 50% larger than the best performing single metal-terephthalate, Cobdc/NF (∼208.2 mA h g−1; 1874 F g−1), followed by Cu-bdc/NF (∼171.3 mA h g−1; ∼1542 F g−1), and last Ni-bdc/NF with∼143.3 mA h g−1 (∼1290 F g−1). The specific capacity of CoCuNi-bdc/NF ranges from ∼191.9−321.3 mA h g−1 (∼1727−2892 F g−1) as current density varied from 40 to 1 A g−1 with ∼77% retention at 10 A g−1 and ∼59% at 40 A g−1. CoCuNi-bdc/ NF displays better electrochemical performance compared to its single component MOFs; hence, CoCuNi-bdc/NF could be the promising electrode material for supercapacitor materials. In the long term, this research would be expandable to a wide range of functional transition-organometallic materials for an energy storage paradigm.